Implementasi Smart City Di Kota Surabaya - Dini Amalia Prawansa; Nanda Nesya; Maulana Tyrta (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The existence of technology brings easy information to the community. Through an application, various information about the city can be accessed quickly by the community and the Regional Government through a program called Smart City. Smart City has been implemented in various cities in the world and is proven to be able to solve various problems quickly too. This information can also be used by the Government to create comfort, security and order as well as a better life. The purpose of writing this article is to get an overview of the smart city concept and its implementation. For this reason, it is necessary to carry out a smart city implementation strategy that is appropriate and in accordance with city conditions. However, of course there are several challenges faced by urban communities and need to be resolved so that smart city development can run smoothly. As for the indicators in determining the success of the Surabaya City Government policy in realizing a smart city according to the Citiasia Center of smart nation (CCSN) in subkhan, F (2017) there are 6 indicators of success in implementing smart city namely, Smart Governance, Smart branding, Smart economy, Smart living, Smart society, Smart environment. Of the 6 indicators, it is expected to provide a good smart city implementation.